THE COMPARISON BETWEEN THE DAILY LANGUAGE AND MEMORY WITHIN THE KURDISH LITERATURE: پەيوەندى نێوان زمان و بير لە چوارچێوەى تيۆرى رێژەيى زمانى - Saeed, Yousif Sharef; Ahmed, Abdul Manaf Ramazan (Journal of Duhok University, 2018)
In this paper the authors demostrated the comparison between the daily language and memory within the kurdish literature and the results was optimistic